A Team-Teaching Initiative to Create Inclusive Chemistry Learning: Fulfilling the Reformed Indonesian Curriculum - Putri, Nova Eliza; Suprihatiningrum, Jamil; Suyanta, Suyanta (Jurnal Pendidikan MIPA, 2024)
Inclusive education aims to provide quality education for all students, regardless of their abilities or backgrounds. This study focuses on the collaboration between chemistry teachers and shadow teachers in delivering inclusive chemistry lessons. The research identifies the collaboration model employed and evaluates its effectiveness. A qualitative phenomenological approach was used, involving chemistry teachers, shadow teachers, and students with disabilities as participants. Students with disabilities in this research such as blind, low vision, and multiple disabilities (cerebral palsy and slow learner). Data were collected through interviews, observations, and document reviews, followed by an interactive analysis based on Miles and Huberman’s model. Findings reveal that inclusive education at Permata High School aligns with national education standards. The collaboration between chemistry teachers and shadow teachers primarily occurs outside the classroom, focusing on learning implementation and assessment rather than lesson planning. The chemistry teacher planned the lesson with the consideration of the shadow teacher as a consultant. As for the implementation in the class, only some subjects on Friday will be assisted by the shadow teacher with permission from students with disabilities. For the subjects that occur on another day, the shadow teacher would get the assessment that needs to be translated. Based on the activities during pre-class, at class, and after class, the collaboration between the chemistry teacher and shadow teacher was categorized as a traditional teaching practice. Key challenges include a disproportionate ratio of disabled students to shadow teachers, limited training for chemistry teachers in inclusive education, and inadequate learning media for complex chemistry concepts.        Keywords: collaborative teaching, inclusive education, shadow teacher, blind, multiple disabilities.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1347-1360